Examining Youth’s Propensity to Political Violence in Northern Nigeria: a Pilot Study Report - Abbo, Usman (2016)
The Northern Nigeria has been experiencing violent conflict ever since the returned of civil rule in 199 ranging from ethno-religious crisis to domestic terrorism. Several studies were conducted in an effort to come to terms with the realities behind this persistence incidence of violence, where factors such as poverty, state failure, unemployment and frustration. However, despite all these studies very little is known about the peculiar environmental factors that makes the Northern Youth particularly more prone to political violence. This is therefore a pilot study which was conducted to explore the socio-cultural and political factors shaping and molding youth’s attitude toward violence in a political context. The findings are intended to inform a wider research project which shall assesses the causes of radicalization of the Almajirai demographic cohort into violent extremism in the North-eastern Nigeria. The study generate the data through a cross-sectional survey, the data was collected from 90 respondents who were randomly selected among the Nigerian students in Universiti Utara Malaysia. The data was analyzed and interpreted using Partial Least Square techniques (PLS), with the aid of smartPLS 2.0. Eight research hypotheses were formulated in which 4 were supported 4 were not supported from the result of the pilot study. Keywords: Youth, Political violence, Terrorism, Insurgency, Nigeri